1990
DOI: 10.1590/s0004-282x1990000400008
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia microcirúrgica da artéria coróidea anterior

Abstract: RESUMO -São apresentadas as características anatômicas da artéria coróidea anterior (AChA), encontradas nas dissecações de 100 hemisférios cerebrais de cadáveres humanos, realizadas sob microscópio cirúrgico.Foi encontrada uma AChA por hemisfério cerebral, 98% originando-se da artéria carótida interna (ACI) 2,4mm distai à origem da artéria comunicante posterior (ACoP) e 4,7mm proximal à bifurcação da ACI. Em 29% dos hemisférios havia ramos perfurantes emergindo da porção comunicante da ACI. A média do calibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Classification of this segment has been provided in detail previously[22632353738394041424344] [Table 3]. …”
Section: Discussionmentioning
confidence: 99%
“…Classification of this segment has been provided in detail previously[22632353738394041424344] [Table 3]. …”
Section: Discussionmentioning
confidence: 99%
“…18,19 Vascularization of the STN The STN is irrigated by the anterior chorioidea arteries, branches of the internal carotid artery, which emerges just above the origin of the posterior communicating artery. 20 The drainage system is of the deep venous type. Through this, the deep cerebral veins, which flow into the internal cerebral vein, drain to the magna vein.…”
Section: Afferent and Efferent Stn Fibersmentioning
confidence: 99%
“…Through this, the deep cerebral veins, which flow into the internal cerebral vein, drain to the magna vein. 20 Neuropathological Considerations Related to the STN Clinical studies of the Luys' STN emerged in 1884, when Ralph Canfield and James J. Putnam presented one of the first case reports of hemiballism. 2 This fact was evidenced in the literature in the study by Martin (1927), apud Parent et al, 2 which reviewed the world literature and found that 11 of the 12 patients previously reported with hemiballism presented lesions in the STN area, including two with lesions restricted to this, in addition to a case reported by the researcher himself of a small hemorrhage almost limited to the STN.…”
Section: Afferent and Efferent Stn Fibersmentioning
confidence: 99%